Contrast‐Enhanced Ultrasound in Patients With COVID‐19: Pneumonia, Acute Respiratory Distress Syndrome, or Something Else?. (12th May 2020) - Soldati, Gino; Giannasi, Gianfranco; Smargiassi, Andrea; Inchingolo, Riccardo; Demi, Libertario
Abstract : Coronavirus disease 2019 (COVID‐19) represents a very heterogeneous disease. Some aspects of COVID‐19 pneumonia question the real nature of ground glass opacities and its consolidative lesions. It has been hypothesized that COVID‐19 lung involvement could represent not only a viral effect but also an immune response induced by the infection, causing epithelial/endothelial lesions and coagulation disorders. We report 3 cases of COVID‐19 pneumonia in which contrast‐enhanced ultrasound was suggestive of consolidations with perfusion defects, at least in part caused by ischemic or necrotic changes and not only by inflammatory or atelectasis events.